2021
DOI: 10.1155/2021/1762584
|View full text |Cite
|
Sign up to set email alerts
|

Participation of Monocyte Subpopulations in Progression of Experimental Endotoxemia (EE) and Systemic Inflammation

Abstract: Systemic inflammation plays a crucial role in formation of various pathological conditions, including sepsis, burns, and traumas. The main effector cells participating in progression of systemic inflammation response and sepsis are monocytes, which regulate both innate and acquired immunity via phagocytosis, synthesis of cytokines and chemokines, antigen presentation, and lymphocyte activation. Thus, the monocytes are considered as a link between innate and acquired immunity. The monocyte subpopulations taken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Thus, the SI allows capturing the morphological variability of the monocyte population during the early stages of sepsis. Indeed, monocytes represent the first line of defence against invading pathogens [ 18 ]. The activation of monocytes induces functional and morphological changes leading to a highly heterogeneous population, especially during the early phases of sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the SI allows capturing the morphological variability of the monocyte population during the early stages of sepsis. Indeed, monocytes represent the first line of defence against invading pathogens [ 18 ]. The activation of monocytes induces functional and morphological changes leading to a highly heterogeneous population, especially during the early phases of sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…They are activated by pattern recognition receptors (PRRs) and sepsis-associated hypoxia [31]. Monocytes control both the innate and adaptive immune responses to pathogens by different mechanisms, including phagocytosis; the release of reactive oxygen species, cytokines, and chemokines; the recruiting of neutrophils; antigen presentation; and the activation of lymphocytes [32].…”
Section: Monocytesmentioning
confidence: 99%
“…Although monocytes have a pivotal role in sepsis, the value of monocyte count for sepsis diagnosis and prognosis is controversial. Some authors reported monocytosis, defined as an increase of monocyte count, while others described monocytopenia associated with increased mortality [32,36]. Thus, the value of monocyte count is limited.…”
Section: Monocytesmentioning
confidence: 99%
“…Monocytes and splenocytes from KD-fed mice show a hyper-inflammatory response to LPS It has been shown that circulating monocytes and splenocytes are necessary for induction of systemic inflammatory cytokines during endotoxemia (26,27). Additionally, we see feeding a diet enriched only in SFAs (KD) leads to enhanced expression of tnf and il-6 in the blood during endotoxemia (Fig 1C, D).…”
Section: Diets Enriched In Sfas Drive Enhanced Responses To Systemic Lps Independent Of the Microbiomementioning
confidence: 70%
“…Endotoxemia mortality results exclusively from a systemic inflammatory response, characterized by an acute increase in circulating inflammatory cytokine levels (ex: TNF, IL-6, and IL-1β) from splenocytes and myeloid derived innate immune cells (monocytes and macrophages) (5,(25)(26)(27). Pre-treatment of monocytes and macrophages with dietary SFAs has been shown to enhance inflammatory pathways in response to microbial ligands, including IL-1β and TNF expression and protein levels (15,28,29).…”
Section: Diets Enriched In Sfas Induce a Hyper-inflammatory Response To Lps And Increased Immunoparalysismentioning
confidence: 99%